ANALISIS YURIDIS PENGGUNAAN WAJAR PADA APLIKASI MEDIA SOSIAL TIKTOK - Sovano, Khalif Raihan (Fakultas Hukum Universitas Islam Indonesia, 2023)
TikTok, a smartphone-based application based on sharing media that provides freedom for users to insert the desired song and sound effects into a short video which will then be ready to be announced and/or uploaded. 1 With the entertainment and comedy genres, TikTok makes teenagers the most dominant demographic even though TikTok's target audience consists of pre-teens to the elderly. Besides that, the consumerist mindset of teenagers makes the demographic perspective of this application user give the impression that the legality element in this application is insignificant and even seems trivial. In this study, the legal aspect in question is copyright. This study carries the formulation of the problem in the form of: 1) What is the legal protection for the original creator of audio and/or video that has been sampled?; 2) What are the provisions governing certainty regarding whether or not a snippet is used by a TikTok application user based on statutory regulations? This research is a normative legal research that uses primary, secondary, and tertiary data sources as a complement or explanation if necessary. The approach used in this study is a statutory approach and a conceptual approach. The results of the research can be concluded: The reasons for the importance of implementing and enforcing fair use in media sharing-based social media applications such as TikTok are: 1) The high potential for copyright infringement occurs because there is no oversight of UserGenerated Content uploaded by users; 2) There is no information that serves as an explanation regarding the use of copyrighted works in applications that can support the certainty of fair use terms; 3) The lack of action to enforce existing provisions in UUHC by the competent authorities has become a catalyst for copyright infringement.